PWE-152 Selective Loss of Oncofoetal Antigen 5T4-Specific T Cell Response Correlates with Progression of Colorectal Cancer. (4th June 2013) - Scurr, M; Davies, M; Phillips, S; Hargest, R; Christian, A; Hockey, T; Williams, G; Gallimore, A; Godkin, A
Abstract : Introduction: The human oncofoetal antigen 5T4 is expressed on many human carcinomas, including colorectal cancer (CRC) cells, but has limited expression on normal tissues making it an ideal target for cancer immunotherapy. Here, a significant loss of T cell response to 5T4 in patients with more advanced CRC has been identified. Methods: Lymphocyte samples obtained from HLA-typed CRC patients and healthy donor controls were cultured for two weeks with pools of overlapping 20mer 5T4 peptides, spanning the entire protein, before subsequent analysis for antigen specificity, as measured by the highly sensitive IFN-g/IL-10 ELISPOT assay. Results: Positive 5T4-specific lines were identified in 79% (15/19) of CRC patients and all (11/11) healthy donors tested. Intriguingly, CRC patients respond to significantly fewer candidate epitopes and generate a lower magnitude of IFN-γ responses to 5T4. Furthermore this response diminishes with tumour advancement despite similar responses to the recall antigen PPD. The mechanism of loss of T cell response is independent of HLA-DR type or patient age, but depletion experiments indicate suppression by Foxp3+ regulatory CD4+ T cells. In addition, analysis of peripheral blood and tumour-infiltrating lymphocytes in the same cohort of patients revealed a marked suppressive phenotype in comparison to healthy age-matched controls. Conclusion: Effective anti-tumour immunotherapy will be reliant upon overcoming such regulation of tumour-specific T cell responses. These data support a rationale for re-stimulating 5T4-specific immune responses in CRC patients, and reducing tumour-induced immunosuppression to enhance immunotherapy. Disclosure of Interest: None Declared.